Relationship between Facebook usage and youth political participation in Nigeria - Abdu, Shamsu Dauda (2017)
Youth political participation is an engaging area of academic research that is evolving. However, studies have recently suggested that traditional form of political participation, especially among youth has been declining in developed and developing countries which may likely create an uncertain future for democracy. Nevertheless, researches have not clearly examined why youth political participation suddenly changed and what is now motivating them to participate. This research examined the relationship between Facebook usage and youth political participation and also addresses why there has been an unprecedented increase in political interest among Nigerian youth in recent years. The study also examined online/offline modes of youth political participation. The present study hypothesized that, Facebook usage significantly relates to youth political participation. The argument is supported by the empirical findings from the quantitative survey of youth (N = 372) in Bauchi metropolis and also from the review of the existing related literature. The results justify that Facebook usage, interactivity with political figures, perceived Facebook information quality and political interest significantly correlates with online/offline political participation among youth. Facebook allows marginalized youth from political activities to interact with weak and strong ties about political issues, share and express their opinions. Conversely, in this study interactivity with political figures does not significant correlate with online political participation. Nonetheless, the findings of this research has reinvigorated the implication of Facebook usage, and present an in-depth knowledge and understanding about Nigerian youth political participation.